The Influence of School Principal Leadership and Organizational Culture on Teacher Performance - Fadilah, Ahmad; Hadiwijaya, Dudung; Muttaqijn, Muhammad Imam (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The purpose of this study is to determine the extent to which organizational culture and school principal leadership influence the performance of educators at SMK Tangerang Global Tangerang. The rationale for conducting this research is rooted in the researcher's belief that issues related to school principal leadership and culture significantly affect teacher performance. Consequently, teacher performance can improve or deteriorate under the direction of the school principal, undoubtedly shaping an organizational culture that demands compliance from school members. Thus, positive organizational culture and the quality of school principal leadership can contribute to improving teacher performance. This research method uses a quantitative approach. Quantitative research produces quantifiable results through the use of statistical procedures or other measurement methods. It is expected that school principal leadership and organizational culture development will be enhanced as a result of this research, thus optimizing teacher performance